Anomalous Heat Diffusion in a Boundary Layer: A Fractionary Blasius’s System - Monteiro, Thiago Bissiatte; Almeida, Alexandre C. L.; Oliveira, Adélcio C. (Journal of Applied Nonlinear Dynamics, 2026)
A model of an anomalous boundary layer over a flat plate was presented through fractional calculus. It is a generalization of Blasius’s system, including a fractional derivative order in the heat equation. A nonlinear differential system with contour condition is usually difficult to solve, in this case, the system has a fractional differential term, therefore a semi-analytical approximation method was used combined with the initial value problem approximation by sequential parameter optimization method. Besides, it was shown that the derivative order has a significant influence on the boundary layer thermal shape and causes a bigger change in the temperature gradient curve.